PHP 5 Power Programming - Gutmans, Andi; Bakken, Stig; Rethans, Derick (Bruce Perens' Open Source series., 2004)
"This book, written by my colleague, Andi Gutmans, and two very prominent PHP developers, Stig Bakken and Derick Rethans, holds the key to unlocking the riches of PHP 5. It thoroughly covers all of the features of this new version, and is a must have for all PHP developers interested in exploring PHP 5's advanced features" -Zeev Suraski, Co-Designer of PHP 5 and Co-Creator of the Zend Engine Expert PHP 5 programming techniques, direct from PHP 5 co-creator and key developers Definitive coverage of the PHP object model, design patterns, XML/SOAP integration, and more Solid introduction and expert insights into performance tuning, PEAR, extensions, and database access The definitive introduction to PHP 5's advanced features! The definitive introduction for today's most powerful PHP 5 techniques In this book, PHP 5's co-creator and two leading PHP developers show you how to make the most of PHP 5's industrial-strength enhancements in any project-no matter how large or complex. Their unique insights and realistic examples illuminate PHP 5's new object model, powerful design patterns, improved XML Web services support, and much more. Whether you're creating web applications, extensions, packages, or shell scripts-or migrating PHP 4 code-here are high-powered solutions you won't find anywhere else. Review PHP's syntax and master its object-oriented capabilities-from properties and methods to polymorphism, interfaces, and reflection Master the four most important design patterns for PHP development Write powerful web applications: handle input, cookies, session extension, and more Integrate with MySQL, SQLite, and other database engines Provide efficient error handling that's transparent to your users Leverage PHP 5's improved XML support-including parsing, XSLT conversions, and more Build XML-based web services with XML-RPC and SOAP Make the most of PEAR: work with the repository, use key packages, and create your own Upgrade PHP 4 code to PHP 5-compatibility issues, techniques, and practical workarounds Improve script performance: tips and tools for PHP optimization Use PHP extensions to handle files/streams, regular expressions, dates/times, and graphics Create original extensions and shell scripts If you're a software developer new to PHP, you'll leap quickly into PHP and its new object-oriented capabilities. If you're an experienced PHP programmer, you already recognize PHP's convenience and simplicity. Now, discover all of its extraordinary pow...